2012
DOI: 10.4103/2231-0770.94804
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome after treatment of Crohn′s disease with mesalamine: Case report and literature review

Abstract: Inflammatory bowel disease and its various treatments may affect the kidney in several ways. Recently, case reports have been published documenting the development of nephrotic syndrome after the treatment for inflammatory bowel disease with 5-aminosalicylic acid derivatives. We report a 50-year-old patient who was diagnosed with Crohn's disease and was treated with mesalamine. The patient subsequently developed nephrotic syndrome and a renal biopsy showed minimal change disease. He was treated with losartan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ambruzs et al reported 4 cases of CD with minimal change disease (5% [4/83]), 3 cases of which were currently taking 5-ASA [ 5 ]. Firwana et al reported a case of CD with minimal change disease with significant improvement in renal function after 5-ASA withdrawal [ 34 ]. Then, 5-ASA-associated interstitial nephritis has received extensive attention [ 5 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ambruzs et al reported 4 cases of CD with minimal change disease (5% [4/83]), 3 cases of which were currently taking 5-ASA [ 5 ]. Firwana et al reported a case of CD with minimal change disease with significant improvement in renal function after 5-ASA withdrawal [ 34 ]. Then, 5-ASA-associated interstitial nephritis has received extensive attention [ 5 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that both conditions may follow a similar pathophysiologic course [23]. There have been a few reports of focal segmental glomerulosclerosis nephrotic syndrome in a patient with UC [24] and CD following mesalamine therapy in patients with nephrotic syndrome [25]. Nevertheless, the causal relationship between the two conditions is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…UC was associated with NS after treatment of UC with mesalazine for 5 years. Firwana et al reported a case of NS after mesalazine treatment for Crohn’s disease [ 5 ]. He also reviewed six case reports of NS after the treatment of UC with 5-amino-salacylic acid derivatives.…”
Section: Case Presentationmentioning
confidence: 99%
“…Previous studies reported that UC patients treated with mesalazine were associated with nephrotic syndrome (NS) [ 5 ]. The relationship between mesalazine and NS is unclear.…”
Section: Introductionmentioning
confidence: 99%